The York Platelet Syndrome: A third case - WHITE, JAMES G. (2010)
Our present study has described a third patient with the York Platelet Syndrome (YPS). The condition consists of a mitochondrial myopathy associated with unique platelet pathology. Their mitochondrial myopathy has not been completely delineated and will be the subject of further study. Platelet pathology in the new patient is essentially identical to that described in the first two patients. Thin sections of her thrombocytes reveal a normal complement of α and δ granules (dense bodies) in some, a decreased number in others and complete absence in a few. The unique pathological feature is the presence of giant organelles, including an intensely electron dense, huge body, the opaque organelle (OO) and a multilayered large body, the target organelle. In addition platelets from the new patient contain large masses and coils of smooth endoplasmic reticulum present infrequently in platelets of the first two patients. The giant opaque and target organelles appear to develop in rough and smooth endoplasmic reticulum of the parent megakaryocyte and mature in the dense tubular system of circulating platelets. The relationship of the unique platelet pathology and mitochondrial myopathy has not been defined.